A Systematic Review of Health Economic Analyses of Housing Improvement Interventions and Insecticide-Treated Bednets in the Home. - Frank Pega; Nick Wilson (PLoS ONE)
Background Housing improvements have considerable potential for improving health. So does the provision of insecticide-treated bednets for malaria prevention. Therefore we aimed to conduct updated systematic reviews of health economic analyses in both these intervention domains. Methods and findings The search strategy included economic analyses of housing improvement interventions and use of insecticide-treated bednets for community-dwelling, healthy populations (published between 1 January 2000 and 15 April 2014). We searched the Cochrane Database of Systematic Reviews, MEDLINE, PubMed, EMBASE, and three health economics databases. Thirty-five economic analyses of seven types of intervention fulfilled the inclusion criteria. Most included studies adopted a health sector perspective and were cost-effectiveness analyses using decision analytic modeling or conducted alongside trials. The overall quality of the studies was generally likely to be adequate for informing policy-making (albeit with limitations in some areas). There was fairly consistent evidence for the cost-effectiveness/favorable cost-benefit of removing indoor lead to prevent lead poisoning and sequelae, and retrofitting insulation to prevent lung disease. But the value of assessing and improving home safety and providing smoke alarms to prevent injuries was more mixed and the economic evidence was inconclusive or insufficient for: home ventilation to prevent lung disease, installing heaters to prevent lung disease and regulating tap water temperatures to prevent scalding. Few studies (n = 4) considered health equity. The 12 studies of providing insecticide-treated bednets or hammocks to prevent malaria found these interventions to be moderately to highly cost-effective. Conclusions This systematic review provides updated evidence that several housing improvement interventions (such as removing indoor lead and retrofitting insulation) and also the provision of insecticide-treated bednets are cost-effective interventions. Nevertheless, for some interventions additional analyses are required to better clarify their health economic and health equity value.